Space for everyone [book with audioplayer] - Wedlick, Seina; Sucre, Camilla; Leigh, Keylor (Library Ideas, LLC, 2025)
This lyrical and heartwarming picture book follows a Nigerian girl who worries about her family's upcoming move. But she soon realizes that no matter where they go, there will always be room at their kitchen table for her community to gather around.